INTERIM CROWNS OF PMMA AND BIS-ACRYL RESIN AND THEIR COLOUR CHANGE IN VARIOUS CONDITIONS-A COMPARATIVE STUDY - Dana Gabriela Budală; Elena Raluca Baciu; Zenaida Surlari; Carina Balcoș; Dragoș Ioan Virvescu (Romanian Society of Oral Rehabilitation, 2021)
Introduction: Provisional restorations must protect the fresh cut enamel, protect the dental pulp, produce occlusal rebalancing and especially restore the lost aesthetic function Data are needed to help predict color stability of provisional resins. The present study was conducted to assess discoloring of PMMA and bis-acrylic based interim crowns in different conditions, after a certain period of time, respectively 7 days and 60 day of submersing the samples both in artificial saliva and in solutions that will cause a change of color. The solutions that we chose were made of artificial saliva and coffee and artificial saliva and green tea, which are the most common beverage among patients.